Free Flow of Sweat due to Loss of Surface Tension at Sweat Droplet Causes Water-Induced Skin Wrinkling - Marasakatla, Soumya; Marasakatla, Karunakar (PeerJ PrePrints, 2013)
Water immersion skin wrinkling appears to be a result of breaking the balance between the pressure within sweat duct and the pressure exerted by the surface tension of sweat droplet at the pore. When a hand is immersed in water, sweat droplets easily merge within the water causing pressure to drop at the pores. The resulted imbalance in pressure makes the sweat within the duct to flow freely into the water. To prevent loss of water from the body and to maintain homeostasis, the body reacts by restricting blood flow to hand causing vasoconstriction and eventual wrinkling of skin.
Keywords: water immersion skin wrinkling; vasoconstriction; homeostasis; surface tension; Cystic Fibrosis; sweat droplet